Aspergillomas of Maxillary Sinus - Z. Průdek (Czech Dental Chamber, 2006)
The variety of clinical findings, possible causes of the illness and its treatment described in this work refer to the patients of the Oral, Jaw and Face Surgery Ward of the hospital in Kyjov and cover a period of three years.